PEMBINAAN MASYARAKAT PESISIR KEPULAUAN KANGEAN UNTUK MENUMBUHKAN KESADARAN PENTINGNYA WAJIB BELAJAR 12 TAHUN STUDI DI DUSUN NYAPLONGONDUNG PULAU KANGEAN - Resdiana, Enza; Alfiyah, Nur Inna (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2019)
Abstract:Education is the main key in advancing the country, so that the government with various educational policy programs targeting all regions in Indonesia at the city, village and island level. However, this policy is constrained when confronted with the ideas of communities that are still traditional, such as in the KangeanIsland which has a relatively low level of education with many cases of dropping out at various levels of education. The aim of the program of community service activities is expected to be able to increase the awareness of the people of the village of Nyaplongondung on the importance of education in the midst of the conditions and thoughts of the community that are still very ordinary and traditional towards the benefits of education. With the provision of guidance it is expected to be able to improve the culture of conscious education, so that people do not be indifferent to the importance of education for their children. This dedication uses qualitative methods with descriptive nature using analysis, referring to data and utilizing theory as supporting material. Community service activities in Nyaplongondung sub-village, Duko village, Arjasa sub-district received very good reception from local agencies namely village apparateurs, institutions such as SDN Bilis-Bilis IV and community of Nyaplongondung.